Evaluation of critical current density and residual resistance ratio limits in powder in tube Nb3Sn conductors. (10th June 2016) - Segal, Christopher; Tarantini, Chiara; Sung, Zu Hawn; Lee, Peter J; Sailer, Bernd; Thoener, Manfred; Schlenga, Klaus; Ballarino, Amalia; Bottura, Luca; Bordini, Bernardo; Scheuerlein, Christian; Larbalestier, David C
Abstract: High critical current density ( J c ) Nb3 Sn A15 multifilamentary wires require a large volume fraction of small grain (SG), superconducting A15 phase, as well as Cu stabilizer with high Residual Resistance Ratio (RRR) to provide electromagnetic stabilization and protection. In powder-in-tube (PIT) wires the unreacted Nb7.5 wt%Ta outer layer of the tubular filaments acts as a diffusion barrier and protects the interfilamentary Cu stabilizer from Sn contamination. A high RRR requirement generally imposes a restricted A15 reaction heat treatment to prevent localized full reaction of the filament that could allow Sn to reach the Cu. In this study we investigate recent high quality PIT wires that achieve a J c  (12 T, 4.2 K) up to ∼2500 A mm −2 and find that the minimum diffusion barrier thickness decreases as the filament aspect ratio increases from ∼1 in the inner rings of filaments to 1.3 in the outer filament rings. We found that just 2–3 diffusion barrier breaches can degrade RRR from 300 to 150 or less. Using progressive etching of the Cu we also found that the RRR degradation is localized near the external filaments where deformation is highest. Consequently minimizing filament distortion during strand fabrication is important for reducing RRR degradation. The additional challenge of developing the highest possible J c must be addressed by forming the maximum fraction of high J c SG A15 and minimizing low J c large-grain (LG) A15 morphologies. In one wire we found that 15% of the filaments had a significantly enhanced SG/LG A15 ratio and no residual A15 in the core, a feature that opens a path to substantial J c improvement.